How to Reduce The Risk of Community-Acquired Pneumonia in Children - Ayu, Ira Marti; Sumayya, Siti; Handayani, Rini; Nitami, Mayumi; Sitanggang, Hendra Dhermawan (Poltekkes Kemenkes Tanjung Karang, 2022)
Overcrowding is one of the factors that contribute to respiratory diseases transmission, including pneumonia. Pneumonia is an infectious disease commonly found and is the most important cause of death for children aged <5. Generally, pneumonia was found in low-income residents from houses overcrowded. This study aims to identify the most dominant risk factors for community pneumonia in children aged <5 years who live in crowded housing in the Work Area of the North Larangan Public Health Center, Tangerang. A case-control study was conducted, with a ratio of cases and controls of 1:1, namely 25 cases and 25 controls. The sampling technique of cases is total sampling, and the control is purposive sampling. This study used univariate, bivariate with chi-square test, and regression logistic for multivariate analysis. Multivariate analysis showed that the risk factors associated with the incidence of pneumonia in children under five who lived in dense housing were exclusive breastfeeding (OR=7.65 (95% CI:1.27-46.07)) and nutritional status (OR=8.79 (95%CI:1.05-73.78)). Reducing the lack of exclusive breastfeeding and improving the underweight dietary status of children can minimize the risk of pneumonia in children under five living in dense housing.